Modelling the transmission behavior of measles disease considering contaminated environment through a fractal-fractional Mittag-Leffler kernel - Wireko, Fredrick A.; Adu, Isaac K.; Gyamfi, Kwame A.; Asamoah, Joshua Kiddy K. (IOP Publishing, 2024)
This article is published by IOP Publishing 2024 and is also available at https://doi.org/10.1088/1402-4896/ad51b0